Measurement of thermal conductivity and viscosity of ZnO-SiO2 hybrid nanofluids - Yalcin, Gokberk; Oztuna, Semiha; Dalkilic, Ahmet Selim; Wongwises, Somchai (SPRINGER, 2022)
Preparing and defining of thermal properties of new type hybrid nanofluids are essential to understand the fluidity mechanism of hybrid nanofluids and select suitable nanofluids in terms of application. This research aims to provide an alternative fluid for different applications and complete the new type of nanofluid necessity in the literature that has been reported by different research groups. In this current investigation, water-based ZnO-SiO2 hybrid nanofluid is prepared by using the two-step method, and thermal conductivity and dynamic viscosity values are experimentally specified. ZnO-SiO2 hybrid nanofluid has 0.5%, 0.75%, and 1% with 50% ZnO-50% SiO2; 33.3% ZnO-66.6% SiO2, and 66.6% ZnO-33.3% SiO2 nanoparticle mixtures. Thermal conductivity and dynamic viscosity are experimentally measured from 20 to 60 degrees C. Maximum thermal conductivity rising is 2.26%, and it is obtained for 1% ZnO0.66-SiO2(0.33) at 50 degrees C. Maximum dynamic viscosity increment is measured as 1.36 times of base fluid for 1% ZnO0.33-SiO2(0.66) at 50 degrees C. Changes in thermal properties are reasonable to use ZnO-SiO2 hybrid nanofluid in different thermal applications to increase system heat transfer rate and efficiency and reduce pressure drop and power consumption. Finally, two different regression equations are developed to predict the thermal conductivity and dynamic viscosity, respectively.
Keywords: Hybrid nanofluids; ZnO; SiO2; Viscosity; Thermal conductivity; Stability; HEAT-TRANSFER APPLICATIONS; DYNAMIC VISCOSITY; ETHYLENE-GLYCOL; RHEOLOGICAL BEHAVIOR; TRANSFER ENHANCEMENT; AQUEOUS NANOFLUIDS; OXIDE NANOFLUIDS; AL2O3; Thermodynamics; Chemistry